Distribution and damage of bacterial canker on lemon bushes in the conditions of the Southern part of Azerbaijan - Guliyev, Farman; Lala, Huseynova (Acta Agraria Debreceniensis, 2022)
This paper summarises and presents the results of two-year (2020–2021) field and laboratory studies on the spread and harmfulness of bacterial canker of citrus crops (Xanthomonas citri (Hasse) Dowson.) on mid-ripening lemon cultivars (Citrus limon L.). Experimental field research conducted by us in 2020–2021. It has been established that bacterial canker (Xanthomonas citri) is found mainly on lemon bushes (Citrus limon L.). The pathogen also causes canker (Xanthomonas citri) on kinkans (Fortunella margarita (Lour) Swingle.), poncirus (Poncirus (L.) Raf.), lime (Cirtus aurantiifolia (Christm.) Swingle.). Japanese cultivars of oranges (Citrus sinensis (L.) Osbeck.) and citron (Citrus medica L.) are distinguished by significant tolerance. The most resistant are tangerines (Cirtus reticulata Blanco.) – they are almost not affected by bacterial canker (Xanthomonas citri). We have established environmental factors that contribute to the wide spread and development of bacterial canker (Xanthomonas citri) on lemon bushes in the southern part of Azerbaijan. The main indicators of the harmfulness of bacterial canker (Xanthomonas citri) have been identified. The potential for the death of canker-infected lemon fruits has been established. The characteristic features of external and internal signs of the disease were established. A scheme for combating bacterial canker (Xanthomonas citri) has been developed, and the optimal concentration of fungicides that retard the growth and development of pathogens has also been established. Photographs of bacterial canker (Xanthomonas citri) damage to lemon fruits are presented.